Factors Determining Caring Behavior of Nurses in the Inpatient Rooms - Susan Irawan Rifai; Dedep Nugraha; Roganda Situmorang (GLOBAL HEALTH SCIENCE GROUP, 2024)
Caring behavior is a very important aspect of nurse practice, because through this behavior nurses can show care, empathy, and concern for patients. Nurses' caring behavior not only has an impact on patient satisfaction, but also on faster patient recovery, adherence to care, and improved treatment outcomes. There are several factors that influence caring behavior, including nurse characteristics, rewards, personality type and work motivation. This study aims to analyze factors associated with caring behavior in nurses. The research design used descriptive correlation with a cross sectional approach to 56 nurses in the inpatient room with a sampling technique using proportionate random sampling. The characteristics of nurses consisted of age, gender, length of service, education level and marital status. The instrument to measure caring behavior uses the Caring Behavior Inventory (CBI-24), while the Eysenck personality inventory contains 24 question items to measure personality type. The results showed that length of work (p=0.015) and work motivation (p=0.015) had a significant relationship with caring behavior, while age (p=0.507), gender (p=0.634), marital status (p=0.146), education (p=0.244), employee status (p=0.529), reward (p=0.737) and personality type (p=0.152) were not related to caring behavior. These results indicate that the longer the nurse works and has high work motivation, the better the nurse's caring behavior will be. Therefore, there is a need for a preceptorship program for new nurses and efforts to increase nurses' work motivation through strategies that support their intrinsic needs and professionalism, especially caring behavior.